К изучению фауны совок Крыма. Сообщение V. Подсемейство Arnphipyrinae (Noctuidae, Lepidoptera) - Ключко, З.Ф. (Вестник зоологии, 1971)
As a result of analysis of three year collection materials, museum materials and data from the literature 94 moth species from Amphipyrinae family are registered in the Crimean fauna, 61 of them being observed for the Crimean peninsula for the first time. Eight species — Autophila limbata S t g г., Apamea platinea T г., Arenostola morrisii Dale , Hydraecia leucographa В k h., Caradrina hypostigma В r s п., С. muricolor В г s п.. Luperina rubella D u p proved to be new for the Ukrainian fauna and L. taurica К I- — new for science. The species of transpalearctic and ponto-mediterranean groups predominate. Specific composition of the subfamily under investigation is very variable in the mountain and very poor in the steppe Crimea.